A better place for whom? Practitioners' perspectives on the purpose of environmental education in Finland and Madagascar. Issue 3 (4th May 2023) - Brias-Guinart, Aina; Aivelo, Tuomas; Högmander, Markus; Heriniaina, Rio; Cabeza, Mar
Abstract: Calls for a common environmental education (EE) vision imply imposing certain values as universal. Nevertheless, there is a lack of knowledge on the extent to which EE reflects universalities versus diverse sociocultural realities. We explored practitioners' perspectives on the purpose of EE by interviewing practitioners in Finland and Madagascar using a theory of change approach. We classified EE goals into eight categories following the framework of Clark et al. (2020 ). We found signs of universal patterns, with commonalities such as the importance of the cognitive domain and de-emphasis of sociocultural aspects. Yet, differences arise: the connection to nature was central in Finland, whereas economic and bridging strategies were more common in Madagascar. Our results reflect the tradition of EE in post-industrial countries and suggest the influence of the colonial legacy and Western epistemologies in Madagascar. Questions remain about the extent to which those differences are culturally grounded. Résumé: Pour une vision commune de l'éducation à l'environnement (EE), il faut imposer certaines valeurs comme universelles. On observe cependant un manque de connaissances sur la mesure dans laquelle l'EE reflète les universalités par rapport aux diverses réalités socioculturelles. Nous avons exploré les perspectives des praticiens sur l'objectif de l'EE en interviewant des praticiens en Finlande et à Madagascar, en utilisant une approche de la théorie du changement. Nous avons classé les objectifs d'EE en huit catégories, selon le cadre de Clark et al. (2020). Nous avons trouvé des signes évocateurs de modèles universels, avec des points communs, comme l'importance du domaine cognitif et la désaccentuation des aspects socioculturels. Pourtant, des différences apparaissent: le lien avec la nature était central en Finlande, tandis que les stratégies économiques et de transition étaient plus courantes à Madagascar. Nos résultats reflètent la tradition de l'EE dans les pays post-industriels et suggèrent l'influence de l'héritage colonial et des épistémologies occidentales à Madagascar. Des questions demeurent quant à la mesure dans laquelle ces différences sont fondées sur la culture.